2017
DOI: 10.1242/jeb.165126
|View full text |Cite
|
Sign up to set email alerts
|

Induced parental care in a poison frog: a tadpole cross-fostering experiment

Abstract: Understanding the external stimuli and natural contexts that elicit complex behaviours, such as parental care, is key in linking behavioural mechanisms to their real-life function. Poison frogs provide obligate parental care by shuttling their tadpoles from terrestrial clutches to aquatic nurseries, but little is known about the proximate mechanisms that control these behaviours. In this study, we used Allobates femoralis, a poison frog with predominantly male parental care, to investigate whether tadpole tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 46 publications
(76 reference statements)
1
14
0
Order By: Relevance
“…A comparison with long-term CMR data of the study population demonstrated site fidelity of females beyond tracking periods, confirming reports on longterm site fidelity in this species (Ringler, Ursprung & Hödl, 2009). Additionally, females showed homing behavior after transporting tadpoles that were experimentally placed on their back (Pašukonis et al, 2017), suggesting benefits of returning to a known site. Females could, for example, profit from experience with a mating partner (Rosenthal, 2017) or enhanced larval survival rate by taking over tadpole transport if the male disappears, which has been demonstrated in A. femoralis (Silverstone, 1976;Ringler et al, 2013;.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…A comparison with long-term CMR data of the study population demonstrated site fidelity of females beyond tracking periods, confirming reports on longterm site fidelity in this species (Ringler, Ursprung & Hödl, 2009). Additionally, females showed homing behavior after transporting tadpoles that were experimentally placed on their back (Pašukonis et al, 2017), suggesting benefits of returning to a known site. Females could, for example, profit from experience with a mating partner (Rosenthal, 2017) or enhanced larval survival rate by taking over tadpole transport if the male disappears, which has been demonstrated in A. femoralis (Silverstone, 1976;Ringler et al, 2013;.…”
Section: Discussionsupporting
confidence: 83%
“…Tracking has been successfully applied to study spatial behavior and navigation in this species. For example, telemetry was used to quantify movements associated with tadpole transport (Beck et al, 2017;Pašukonis et al, 2017) or to demonstrate that A. femoralis males return to their home territory from several hundred meters after translocation (Pašukonis et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…When and how exactly frogs learn about specific pools within their local habitat remains open for further investigation. The recent discovery that tadpole transport can be experimentally initiated via adding tadpoles to a frogs’ back could serve as a powerful technique to answer these questions (Pašukonis et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that suitable water sites for tadpole deposition seem to be a limiting resource in A. femoralis (Ringler, Hödl, et al., ) and that spatial memory plays an important role in the reproductive behaviour of this species (Beck et al., ; Pašukonis, Warrington, Ringler, & Hödl, ; Pašukonis et al., ). Transporting males usually follow straight trajectories to and between deposition sites (Beck et al., ; Pašukonis et al., ). This is indicative of active decision‐making prior to the actual transporting movement rather than a random or guided search to find deposition sites.…”
Section: Introductionmentioning
confidence: 99%
“…A. femoralis is active in leaf litter or on fallen tree trunks on the forest floor, with males exhibiting territorial behavior ( Roithmair, 1992 ; Montanarin, Kaefer & Lima, 2011 ). Females lay eggs on dead leaves in male territories during the rainy season, and males use water bodies ranging from shed palm bracts, Brazil-nut capsules, puddles on fallen tree trunks, peccary wallows and temporary puddles on the forest floor to deposit tadpoles after hatching ( Roithmair, 1994 ; Gascon, 1995 ; Ringler, Ursprung & Hödl, 2009 ; Beck, Thebpanya & Filiaggi, 2010 ; Ringler, Hödl & Ringler, 2015 ; Pašukonis et al, 2016 , 2017 ). The availability and location of sites for tadpole deposition influences year-to-year displacement of individuals that survive more than one breeding season ( Ringler, Ursprung & Hödl, 2009 ).…”
Section: Methodsmentioning
confidence: 99%